Sistem Informasi Administrasi Pengelolaan Surat Di Organisasi Berbasis Web - , Kartini; , Azizah Fatmawati, S.T., M.Cs (2017)
Administration is an activity that includes setting purpose and establishing ways of organizing coaching organization. One of these activities are outgoing mail and incoming mail. Outgoing mail and incoming mail is needed in the organization, especially in the secretarial field. Nowdays, many number of letters made and received in the administration using a conservative system. Conservative system will be require a long time and requires a lot of energy. Regional Leaders 'Aisyiyah Surakarta has a broad role towards society will require administrative information systems management letter on the web-based organization. The development of such systems is expected to reduce the burden of data management letter on Regional Leaders 'Aisyiyah Surakarta. Development of the system aims to simplify and speed in the management, collectiin and search incoming and outgoing mail. In another hand, it can be work effectively and efficiently. Research methodology using field study includes interviews, observation and review of the literature. Wterfall development method used starting the investigation, analysis, design, implementation and testing. Development of web-based information system is implemented using Cascading Style Sheet (CSS), JavaScript and Programming Hypertext Preprocessor (PHP) as a programming language, MySQL as its database. The results of the administrative information systems developed in organizations simplify the management letter. It is based on black box testing with results valid while the test results of questionnaires with a precentage of 83% is the system according to the needs of the management letter.